Cet obscur objet de désir : à propos de la construction want GN et de ses gloses - Philippe Muller (Corela)
After reintroducing some diachronic elements about the development of the notions of desire and volition for want - a verb originally associated with an idea of deficit or lack - this paper aims to study the semantics of the want NP construction. It is proposed that the notion of deficit should be integrated into its modern meaning, a point which is only tacitly acknowledged in some hypotheses arguing that this construction can be systematically rephrased with the help of a deleted element - ranging from a verb to an abstract preposition. These approaches are understood as trying to account for the fact that the notions want NP expresses today are semantically always situated beyond that of deficit, a state of affairs which is achieved through a covert embedded relation. These views are first critically assessed so that their systematicity is questioned. It is then proposed, in an enunciative approach, that the concept of prospective validation and Culioli’s topological representation of the notional domain are relevant to account for the construction of the notions of desire and volition from that of deficit. This claim raises the issue of the management of cognitive otherness, which is central in predicting the meaning of some want-constructions that are not addressed in those hypotheses.